HUMOR AND SATIRE IN W . SHAKESPEAR'S COMEDIES - Eldorbek Hamitov Erkinovich; Zarina Abdiyeva (Лучшие интеллектуальные исследования, 2024)
This article delves into the multifaceted world of humor and satire within William Shakespeare's comedies. Through an examination of select plays such as "Twelfth Night," "As You Like It," and "A Midsummer Night's Dream," it explores the ways in which Shakespeare employed various comedic techniques to entertain and provoke thought among his audiences. From witty wordplay and farcical situations to biting social commentary and satire, Shakespeare masterfully crafted his comedies to both amuse and challenge societal norms of his time. By analyzing the comedic elements within these plays, this study seeks to shed light on Shakespeare's enduring relevance as a playwright whose humor continues to resonate with audiences across centuries and cultures.